2005
DOI: 10.1086/425905
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Cytomegalovirus Load Decrease in Solid‐Organ Transplant Recipients after Preemptive Therapy with Valganciclovir

Abstract: The availability of valganciclovir (VGCV) has significantly simplified the treatment of human cytomegalovirus (HCMV) infection after solid-organ transplantation. We show that there was no difference in the kinetics of the decrease in HCMV load after preemptive therapy with VGCV in 22 solid-organ transplant recipients (T1/2=2.16 days), compared with that in 23 patients treated with intravenous ganciclovir (GCV) (T(1/2) = 1.73 days; P=.63). Preemptive therapy with VGCV provides control of HCMV replication that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 14 publications
3
81
1
2
Order By: Relevance
“…There is good clinical data to support the use of valganciclovir for the treatment of CMV after solid organ transplantation [81] . Viral kinetic studies showed comparable viral decay between IV ganciclovir and valganciclovir [50] . In a recent study, 321 solid organ (including liver) transplant recipients with non-severe CMV disease were randomized to valganciclovir or IV ganciclovir for a fixed 21-d course, followed by valganciclovir maintenance treatment for 4 wk; the proportion of patients with viral eradication at 21 and 49 d were comparable in the IV ganciclovir and valganciclovir groups (Figure 2) [81] .…”
Section: Treatment Of CMV Disease After Liver Transplantationmentioning
confidence: 92%
See 2 more Smart Citations
“…There is good clinical data to support the use of valganciclovir for the treatment of CMV after solid organ transplantation [81] . Viral kinetic studies showed comparable viral decay between IV ganciclovir and valganciclovir [50] . In a recent study, 321 solid organ (including liver) transplant recipients with non-severe CMV disease were randomized to valganciclovir or IV ganciclovir for a fixed 21-d course, followed by valganciclovir maintenance treatment for 4 wk; the proportion of patients with viral eradication at 21 and 49 d were comparable in the IV ganciclovir and valganciclovir groups (Figure 2) [81] .…”
Section: Treatment Of CMV Disease After Liver Transplantationmentioning
confidence: 92%
“…The risk of CMV disease after liver transplantation is associated, in direct proportion, with the degree of CMV replication, which is partly a function of overimmunosuppression [8,23,49,50] . In one study, a viral load of 1-2860 CMV copies/10 6 peripheral blood mononuclear cells (PBMC) increased CMV disease risk by nine-fold, while viral loads > 2860/10 6 PBMC increased the risk by 50-fold [8] .…”
Section: Degree Of Viral Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of CMV disease after li ver transplantation is asso ciated, in direct proportion, with the degree of CMV rep lication, which is partly a function of overimmunosup pression [9,24,55,56] . Other factors associated with CMV dis ease after li ver transplantation include cold ischemia time, bacterial and fungal infections and sepsis, the amount of blood loss, fulminant hepatic failure as the indication for liver transplantation, age, female gender, Hispanic race, and renal insufficiency [2,3,20,57] .…”
Section: Other Factorsmentioning
confidence: 99%
“…The basic principle of preempti ve therapy is to detect the presence of CMV replication prior to the onset of clinical symptoms, so that antiviral therapy is administered early i n order to prevent the progressi on of asymptomati c i nfec tion to fullblown clinical disease [56,58,59,61,66] . Preemptive therapy has the potential advantage of targeting therapy to the highest risk patients and thereby decreasing drug costs and toxicity.…”
Section: Preemptive Therapymentioning
confidence: 99%